Manhaj Dakwah Sheikh Haji Muhammad Waly Al-Khalidy in Aceh:: A Study on the Preservation of the Tawheed - Gunandar, Jerri; Najihah, Najihah (Jurnal Ilmiah Teunuleh, 2024)
This article explores the da'wah methodology of Shaykh Haji Muhammad Waly Al-Khalidy, a significant clerical figure in Aceh known for his efforts in preserving the creed of tawhid and advancing da'wah in the region. The study focuses on his community engagement, particularly within Islamic boarding schools and through public lectures (syarahan). It aims to evaluate the impact of his da'wah from historical and contemporary perspectives. The research employs two primary methodologies: library research and field research. The library research involves reviewing previous studies and analyzing various texts related to da'wah and tawhid preservation. Key references include works by Prof. Dr. Muhibuddin Waly, titled "Ayah Kami: Syeikhul Islam Abuya Muhammad Waly Al-Khalidy, Bapak Pendidikan Aceh," and Ustad Musliadi's "Syaikhul Islam Aceh, Tokoh Pendidikan dan Ulama 'Arif Billah," along with writings by Shaykh Haji Muhammad Waly Al-Khalidy himself. Field research incorporates interviews to gather accurate data from credible sources. Findings indicate that Shaykh Haji Muhammad Waly Al-Khalidy has made significant contributions to Islamic development, particularly in maintaining the tawhid creed. His efforts include direct preaching within communities and educating students in Aceh, leading to the emergence of many knowledgeable scholars who uphold the principles of Ahli Sunnah wal Jamaah. Overall, this study highlights the enduring legacy of Shaykh Haji Muhammad Waly Al-Khalidy in promoting a correct understanding of tawhid and fostering a new generation of scholars dedicated to preserving Islamic teachings in Aceh.